Cupidesulfovibrio liaohensis gen. nov., sp. nov., a novel sulphate-reducing bacterium isolated from an oil reservoir and reclassification of Desulfovibrio oxamicus and Desulfovibrio termitidis as Cupidesulfovibrio oxamicus comb. nov. and Cupidesulfovibrio termitidis comb. nov - Wan, Yun Yang; Luo, Na; Liu, Xiao-Li; Lai, Qi-Liang; Goodfellow, Michael (International journal of systematic and evolutionary microbiology, 2021)
A novel sulphate-reducing, Gram-stain-negative, anaerobic strain, isolate XJ01 T , recovered from production fluid at the LiaoHe oilfield, PR China, was the subject of a polyphasic study. The isolate together with Desulfovibrio oxamicus NCIMB 9442 T and Desulfovibrio termitidis DSM 5308 T formed a distinct, well-supported clade in the Desulfovibrionaceae 16S rRNA gene tree. The taxonomic status of the clade was underscored by complementary phenotypic data. The three isolates comprising the clade formed distinct phyletic branches and were distinguished using a combination of physiological features and by low average nucleotide identity and digital DNA–DNA hybridization values. Consequently, it is proposed that isolate XJ01 T represents a novel genus and species for which the name Cupidesulfovibrio liaohensis gen. nov., sp. nov. is proposed with the type strain XJ01 T (=CGMCC 1.5227 T =DSM 107637 T ). It is also proposed that D. oxamicus and D. termitidis be reclassified as Cupidesulfovibrio oxamicus comb. nov. and Cupidesulfovibrio termitidis comb. nov., respectively.